2016
DOI: 10.1152/japplphysiol.00014.2016
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate supplementation: impact on skeletal muscle vascular control in exercising rats with chronic heart failure

Abstract: Chronic heart failure (CHF) results in central and peripheral derangements that ultimately reduce skeletal muscle O2 delivery and impair exercise tolerance. Dietary nitrate (NO3 (-)) supplementation improves skeletal muscle vascular function and tolerance to exercise. We tested the hypothesis that NO3 (-) supplementation would elevate exercising skeletal muscle blood flow (BF) and vascular conductance (VC) in CHF rats. Myocardial infarction (MI) was induced (coronary artery ligation) in young adult male rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 61 publications
3
39
1
Order By: Relevance
“…However, there is increasing evidence for a specific role of this particular characteristic of the anions in patients with HF (Coggan and Peterson, 2016). A recent study in rats that develop HF after induction of MI by coronary artery ligation (Ferguson et al, 2016) has demonstrated the benefits of dietary nitrate treatment. At 21 days after coronary artery occlusion, rats were randomized to 5 days of nitrate-rich (1 mmol/kg per day nitrate) versus nitrate-deplete beetroot juice and underwent investigations of skeletal muscle blood flow and vascular conductance.…”
Section: B Nitrite and Nitrate In Exercise And Muscle Biologymentioning
confidence: 99%
“…However, there is increasing evidence for a specific role of this particular characteristic of the anions in patients with HF (Coggan and Peterson, 2016). A recent study in rats that develop HF after induction of MI by coronary artery ligation (Ferguson et al, 2016) has demonstrated the benefits of dietary nitrate treatment. At 21 days after coronary artery occlusion, rats were randomized to 5 days of nitrate-rich (1 mmol/kg per day nitrate) versus nitrate-deplete beetroot juice and underwent investigations of skeletal muscle blood flow and vascular conductance.…”
Section: B Nitrite and Nitrate In Exercise And Muscle Biologymentioning
confidence: 99%
“…12 Thus, circulating nitrate/nitrite may serve as an alternative pool for bioactive NO, which can sustain/enhance NO signaling when the traditional pathway for NO generation is less functional. 9, 13 Indeed, nitrate/nitrite supplementation has been shown to increase blood flow to exercising muscle in rats with 14, 15 and without 16, 17 heart failure. NO-induced vasodilation during exercise may facilitate the matching of perfusion to metabolic activity.…”
Section: Introductionmentioning
confidence: 99%
“…As this activation is known to lead to increases in maximal power output, particularly in type II fibers, it lends further support to nitrate’s efficacy in CHF (where patients are known to be more type II-fiber dominant). In further support of these findings, 2 separate CHF rat model studies, 1 using an acute dose (5 mg/kg sodium nitrite) and 1 using a chronic dose (1 mmol nitrate/kg/day for 5 days), demonstrated significant increases in blood flow and vascular conductance in skeletal muscle [ 38 , 39 ]. The acute sodium nitrite infusion also showed a preferential increase in blood flow, specifically in the muscles of the rats with a higher percentage of both type IIb + IId/x fast-twitch fibers [ 38 ].…”
Section: Introductionmentioning
confidence: 94%